Comparison of Entrepreneurial Ecosystems of South Korea, Thailand and Vietnam - Ha, Thai Thanh (Department of Public Administration, Parahyangan Catholic University, 2025)
This research conducts a comparative analysis of entrepreneurial ecosystems across South Korea, Thailand, and Vietnam utilizing the most recent Global Entrepreneurship Monitor data to examine key ecosystem components. The investigation reveals substantial disparities in ecosystem maturity levels among these nations through the analysis of Pearson partial correlations between entrepreneurial ecosystem elements. By identifying distinct variations in ecosystem characteristics and associated entrepreneurial activities, this study proposes targeted policy recommendations for strengthening startup and micro, small, and medium enterprises development frameworks within these three Asia-Pacific countries. The findings contribute to the broader understanding of entrepreneurial ecosystem development in regional public policy contexts, while acknowledging research limitations and suggesting future directions for enhanced generalizability through more comprehensive investigations.